2022
DOI: 10.22454/fammed.2022.922801
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Children’s Preventive Health Services During the COVID-19 Pandemic

Abstract: Background and Objectives: Stay-at-home orders, social isolation recommendations, and fear of COVID-19 exposure have led to delays in children’s preventive health services during the pandemic. Delays can lead to missed opportunities for early screening and detection of health problems, and increased risks for outbreaks of vaccine-preventable diseases. Understanding prevalence of and reasons for missed, delayed, or skipped preventive health services is important for developing strategies to achieve rapid catch-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
5
13
0
1
Order By: Relevance
“…The results of this study suggest that 27.6% of US children aged 0 to 17 years had delayed or missed preventive care due to the COVID-19 pandemic, which is consistent with the limited available research in this area. [3][4][5] We observed that several predisposing, enabling, and need factors were associated with delayed or missed pediatric preventive care, with differences by racial and ethnic group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of this study suggest that 27.6% of US children aged 0 to 17 years had delayed or missed preventive care due to the COVID-19 pandemic, which is consistent with the limited available research in this area. [3][4][5] We observed that several predisposing, enabling, and need factors were associated with delayed or missed pediatric preventive care, with differences by racial and ethnic group.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] Studies examining the prevalence of delayed or missed pediatric preventive care during the COVID-19 pandemic in a nationwide sample of US children are scarce, and only a few have explored potential determinants. 4,5 Such studies did not examine potential risk factors such as child age, main caregiver physical or mental health, home ownership, having a usual source of pediatric preventive care, having a personal doctor or nurse, perceived child health, and evaluated child health, 4,5 which may have resulted in residual confounding, because such factors may affect health care access and use. 18,19 Further, previous studies 4,5 did not examine associations by child racial and ethnic group, which may have precluded the identification of race and ethnicity-specific risk and protective factors for delayed or missed pediatric preventive care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, this study was conducted between 2021 and 2022 during the COVID-19 pandemic. According to Nguyen et al (2022), the pandemic affected the number of well-child visits, with one-quarter of parents delaying or canceling their appointments [ 38 ]. Thus, these conditions may have affected the number of well-child visits in the present study.…”
Section: Discussionmentioning
confidence: 99%